From botany to bedside: a review of the health benefits of Lycium barbarum as a functional food - Alois Berisha; Elena-Alexandra Alexa; Robbie Kelleher; Tao Zhang (Exploration of Foods and Foodomics)
Native to East Asia and predominantly cultivated in regions such as the Ningxia Hui and Xinjiang Uyghur Autonomous Regions of China, Lycium barbarum (L. barbarum), commonly known as goji berry, has a long history in traditional medicine and is gaining recognition in contemporary health research. This review provides a comprehensive exploration of its botanical characteristics, pharmacokinetics, and safety, alongside a critical evaluation of human clinical studies investigating its therapeutic potential. Key health benefits include immune modulation, antioxidative effects, mental health support, ocular health preservation, and metabolic and cardiovascular regulation. Furthermore, its role in addressing age-related macular degeneration and chronic conditions such as cancer and metabolic syndrome is highlighted. The bioactivity of L. barbarum is attributed to its rich composition of polysaccharides, carotenoids, flavonoids, and other bioactive compounds, which exhibit anti-inflammatory, neuroprotective, and metabolic-regulating properties. This review also examines the safety profile of L. barbarum, considering its side effects, toxicity, potential contamination, and interactions with medications, emphasising the importance of balancing its health-promoting properties with cautious consumption. Despite promising findings, gaps in the evidence base, including the need for larger, long-term, and rigorously controlled trials, remain significant barriers to clinical translation. By integrating traditional medicinal knowledge with modern scientific insights, this review underscores L. barbarum’s potential as a functional food and therapeutic agent. Its unique pharmacological properties and broad applicability position it as a valuable tool for health promotion and disease prevention, while highlighting areas requiring further research to optimise its safe and effective use.